Mastering the Skills Gap at Systemic Level – The Education Management Information System: A Key Element for an Effective Digital Transformation in Education - Daniel BŐJTE (Revista de Management Comparat International)
Educational leaders must make informed predictions in order to design and adopt relevant educational strategies to bridge the skills gap, so they need reliable and trustworthy data. A well designed and properly rolled-out Education Management Information System (EMIS) will assure precise, fluid and timely datasets which can be easily interpreted, being able to extract the insights needed by using the adequate tools for data analysis, filtering out redundant or irrelevant metrics. Being not only an IT tool and a database, but rather a system within a larger education system, EMIS contributes to implement the policies and practices by which higher education institutions effectively collect, protect and use digital information assets to meet academic and business needs. This paper highlights the role and the importance of an effective EMIS and the biggest challenges in implementing it.